Pelatihan dan Implementasi Public Speaking di Kalangan Siswa SMA - Witanti Prihatiningsih; Aan Setiadarma; Musa Maliki (Universitas Persada Indonesia YAI, 2023)
Public speaking is an important skill for everyone to master, especially for those who are inthe field of communication including politics and leadership. Regarding this context, this articleis the result of community service program that aims to provide an understanding of publicspeakings to students at the Fithrah Insani Islamic Senior High School. Moreover, this eventprovides the students a proper training on how they can basically practice public speaking. Thisseries of activities includes providing basic and advance understanding of public speaking aswell as practising it in front of class. In conclusion, after the public speaking training, studentsare able to explain the basics of public speaking, overcome nervousness or anxiety, and are ableto implementing public speaking in front of the class.